Modeling quantum cascade lasers: Coupled electron and phonon transport far from equilibrium and across disparate spatial scales. Issue 6 (28th December 2016) - Shi, Y. B.; Mei, S.; Jonasson, O.; Knezevic, I.
Abstract : Quantum cascade lasers (QCLs) are high‐power coherent light sources in the midinfrared and terahertz parts of the electromagnetic spectrum. They are devices in which the electronic and lattice systems are far from equilibrium, strongly coupled to one another, and the problem bridges disparate spatial scales. We present our ongoing work on the multiphysics and multiscale simulation of far‐from‐equilibrium transport of charge and heat in midinfrared QCLs.